Influence Work Environment, Intrinsic motivation, and Work Discipline to Employee Performance at BPKAD Bantul Regency - Alfi Nur Luluk Chudhaifah; Didik Subiyanto; Nala Tri Kusuma (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This study aims to determine the effect of work environment, intrinsic motivation, and work discipline on employee performance of the Bantul Regency Financial, Revenue and Asset management Agency. In the process of archieving organizational goals, employee performance is an important factor cannot be ignored. This research uses a quantitive approach by distributing questionnaires to 80 respondents who are the entire population in the agency. The data analysis technique used is multiple linear regression to determine the relationship between variabels. The results showed that three independent variabels namely work environment, intrinsic motivation, and work discipline have a positive influence on work performance, both simultaneousy and partially. These results show that a supportive work atmosphere, empuragement from within, and compliance with the rules, indeed play a major role in increasing employee productivity. The research is expected to be a reference and improvement for the Bantul Regency Regional Financial, Revenue, and Asset Management Agency in increasing employee motivation, work environment, work discipline and employee performance so that they can increase and organizational goals can be archieved.